Peranan Just in Time Method dalam Upaya Mengeliminasi Non Value Added Activity di Perusahaan: Literature Review - Bahiizza Shadrina Zhafarin; Hani Putri; Jahira Fajri Madani; Acim Heri Iswanto; Nadya Salsabila; Natasya Nazla; Zahra Septina; Muhammad Fawwaz (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
The development of technology that occurs today also has an impact on increased market competition. Every company must be able to increase productivity effectively and efficiently. Companies must also be able to minimize waste that becomes production losses. This study aims to analyze and determine the role of just in time methods in reducing wasteful activities in the company. This research is a literature review originating from several online sites such as Google Scholar and Refseek by including the keywords “just in time method” and “eliminating non value added activity”. The inclusion criteria used are regarding the role of the just in time method in eliminating non value added activities. The results found from research that in an effort to improve product quality and production cost efficiency companies can apply the just in time method. This must also be balanced with the company’s ability to prepare human resources that work well and adequately. Thus, efforts to minimize waste can be guaranteed and the company reaches benefits.